(untitled) (Journal of the Bangladesh Agricultural University, 2019)
The focus of the study was to evaluate the comparative profitability of sole pineapple, pineapple-papaya and pineapple-banana-arum cultivation at Madhupur and Ghatail Upazilas of Tangail district in Bangladesh. Data from 90 randomly selected farmers, 30 each from sole pineapple, pineapple-papaya and pineapple-banana-arum categories, were collected through face-to-face interview using a set of pre-tested questionnaires. Profitability analysis was used to estimate the comparative profitability and Cobb-Douglas type production function technique was used to identify the factors influencing gross return. The major findings of the study revealed that sole pineapple, pineapple-papaya and pineapple-banana-arum cultivation in the study areas were profitable, among which, pineapple-papaya cultivation was relatively more profitable than the two other patterns. It was evident from Cobb-Douglas type production function that seed, human labour, fertilizer, insecticide, power tiller, and manure had a significant impact on gross return from sole pineapple, pineapple-papaya, pineapple-banana-arum production. J. Bangladesh Agril. Univ. 17(2): 236–243, June 2019